Bioactive polysaccharides and their soluble fraction from Tossa jute (Corchorus olitorius L.) leaves. (October 2020) - Ben Yakoub, Amira Racha; Abdehedi, Ola; Jridi, Mourad; Elfalleh, Walid; Bkhairia, Intidhar; Nasri, Moncef; Ferchichi, Ali
Abstract: The biological proprieties of mucilaginous polysaccharides (PSc) and their soluble fraction (SF) extracted from Tossa jute leaves ( Corchorus olitorius L.) using an ethanol precipitation method were studied. The results showed that PSc had higher total polyphenols and flavonoids and greater antioxidant activities than SF. At 1.5 mg/ml PSc, the antioxidant activities were about 90% against 1, 1-diphenyl-2-picryl hydrazyl radical (DPPH), 78% against lipid peroxidation and 69% against β-carotene. The PSc with a FRAP assay at the same concentration showed an effective protection against hydroxyl radicals and DNA breakage. Furthermore, the extracted PSc had a wide spectrum of antibacterial activities against all bacteria tested (Gram+ and Gram-) while SF was effective against Klebsiella pneumoniae and Salmonella enterica at 25 mg/ml. The overall data suggested that this natural PSc may be used as a competitive antioxidant and antimicrobial additive in food and in medicinal preparations. Graphical abstract: Image 1 Highlights: Polysaccharides (PSc) were extracted from Tossa jute ( Corchorus olitorius L.) leaves. PSc had high total sugar content. PSc showed higher antioxidant activities than the soluble fraction (SF). Tossa jute PSc and their SF showed high antibacterial activities.